Silent voices of the midwives: factors that influence midwives' achievement of successful neonatal resuscitation in sub-Saharan Africa: a narrative inquiry - Jan Becker; Chase Becker; Florin Oprescu; Chiung-Jung (Jo); James Moir; Meshak Shimwela; Marion Gray (BMC, 2022)
Abstract Background In Tanzania, birth asphyxia is a leading cause of neonatal death. The aim of this study was to identify factors that influence successful neonatal resuscitation to inform clinical practice and reduce the incidence of very early neonatal death (death within 24 h of delivery). Methods This was a qualitative narrative inquiry study utilizing the 32 consolidated criteria for reporting qualitative research (COREQ). Audio-recorded, semistructured, individual interviews with midwives were conducted. Thematic analysis was applied to identify themes. Results Thematic analysis of the midwives' responses revealed three factors that influence successful resuscitation: 1. Hands-on training ("HOT") with clinical support during live emergency neonatal resuscitation events, which decreases fear and enables the transfer of clinical skills; 2. Unequivocal commitment to the Golden Minute® and the mindset of the midwife; and. 3. Strategies that reduce barriers. Immediately after birth, live resuscitation can commence at the mother's bedside, with actively guided clinical instruction. Confidence and mastery of resuscitation competencies are reinforced as the physiological changes in neonates are immediately visible with bag and mask ventilation. The proclivity to perform suction initially delays ventilation, and suction is rarely clinically indicated. Keeping skilled midwives in labor wards is important and impacts clinical practice. The midwives interviewed articulated a mindset of unequivocal commitment to the baby for one Golden Minute®. Heavy workload, frequent staff rotation and lack of clean working equipment were other barriers identified that are worthy of future research. Conclusions Training in resuscitation skills in a simulated environment alone is not enough to change clinical practice. Active guidance of "HOT" real-life emergency resuscitation events builds confidence, as the visible signs of successful resuscitation impact the midwife's beliefs and behaviors. Furthermore, a focused commitment by midwives working together to reduce birth asphyxia-related deaths builds hope and collective self-efficacy.